identifikasi identifikasi faktor penyebab keputihan pada remaja putri - Sari. AZ, Winna Kurnia (SCIENTIA JOURNAL, 2019)
Vaginal discharge is out fluid besides blood from vaginal glands outside the habit, either smelling or not, and accompanied by a local itch. The treatment factors that affect vaginal discharge are attitude, motivation, exposure of information, and parents of vulva hygiene. The purpose of this study is to know the relationship of attitude, motivation of informational exposure, and the role of parents to vulva hygiene with vaginal discharge at adolescent girls at SMAS Pertiwi of Jambi city 2018. This type of research uses analytic survey method with cross sectional approach. Population of this research is all schoolgirl class X and XI in SMAS Pertiwi Jambi which amounted to 86 people. The sample taken in this study is total population data collecting technique in this study using primary data with questionnaire data analysis using chi square statistic. The result of the research is attitude relationship (p value 0,001), motivation (p value 0,029), exposure of information (p value 0,000), parents role (p value 0,006), vulva hygiene (p value 0,001) with vaginal discharge. For statistic logistic regression there is the most dominant variable to the vaginal discharge of female adolescent in SMAS Pertiwi of Jambi city, that is the variable of information exposure with p value - 0,056. The conclusion of this study is that the variable of information exposure simultaneously with the vulva hygiene variable affects vaginal discharge. Advice on young women to know the causes and dangers of vaginal discharge so them can improve the quality of health, especially reproductive health.